The Value of Wellness-Related Courses in Higher Education - Pepin, Kristen R.; Sawyer, Jason C. (Building Healthy Academic Communities Journal, 2022)
Background: General education curriculums provide students with knowledge and skills that empower them to engage in their communities and prepare them for life after graduation. Furthermore, colleges and universities can establish campus culture and express their values through their general education curriculum. Aim: The aim of this article was to inspire faculty and administrators to reflect on the wellness culture present at their institution, specifically within their general education program. Methods: The authors addressed the need for a campus-wide wellness-related general education course. Arguments against and benefits of such a course were presented, as were suggestions for future research. Results: Wellness is a pertinent topic woven throughout our lives and the lives of our students. Attending college offers students newfound independence and autonomy, as well as an opportunity to develop positive lifelong habits. A wellness-related course reinforces the holistic, interdisciplinary approach to general education and teaches the importance of healthy behaviors. Conclusion: Although concerns surrounding institutional resources exist when considering the creation of a new campus-wide requirement, the potential improvements in academic performance, student retention, and health behaviors outweigh the challenges.